Intramuscular vs. Intradermic Needle-Free Vaccination in Piglets: Relevance for Animal Welfare Based on an Aversion Learning Test and Vocalizations - Dalmau, Antoni; Sánchez-Matamoros, Almudena; Molina, Jorge M.; Xercavins, Aida; Varvaró-Porter, Aranzazu; Muñoz, Israel; Moles, Xènia; Baulida, Berta; Fàbrega, Emma; Velarde, Antonio; Pallisera, Joaquim; Puigredon, Alba; et al. (Frontiers in Veterinary Science, 2021)
The aim of the present study was to compare intramuscular injection with a needle and intradermic needle-free vaccinations against porcine reproductive and respiratory syndrome (PRRS) in piglets at 28 days old by studying behavioural and physiological reactions. A total of 72 piglets divided into two sex-balanced batches were assessed. Within each batch, piglets were divided into three treatments, that were Hipradermic (0.2 mL of UNISTRAIN® PRRS vaccine administered with an intradermic needle-free device), Intramuscular (IM, 2.0 mL of vaccine) and Control (not vaccinated). Before the vaccination piglets were trained to cross 4m long raceway to perform an aversion learning test. The day of vaccination, the time taken to cross the raceway was registered per each piglet at different times: prior to the vaccination, 10 min, 2h, 24h, 48h and 72h after the vaccination, to measure variations in these times as signs of aversion to the vaccination process. Vocalizations, as potential signs of pain, were recorded as well at the end of this raceway to analyse their frequency (Hz), duration and level of pressure (dB) at the moment of vaccination. Salivary cortisol, as a sign of the HPA-axis activity, was assessed 10 min after the vaccination. In addition, activity budgets, local reaction to the vaccine and serological titre were also considered in the study. Ten min after the vaccination, IM piglets took longer (P<0.001) to cross the raceway than did Hipradermic and Control piglets. Vocalizations were significantly different between the three treatments: Control piglets produced vocalisations with the lowest frequency (P<0.001) and level of pressure (P<0.001), and IM with the highest, with Hipradermic in a significant intermediate position (P<0.001). Accordingly, the day of the vaccination, IM and Hipradermic animals were lying on the side of the vaccine administration a greater proportion of time than were Control piglets (10%, 11% and 6%, respectively; P = 0.027). Salivary cortisol was not significantly different between treatments. Serum titre of antibodies against PRRS was higher (P<0.001) in both vaccinated treatments, in comparison to Control piglets. It is concluded that the Hipradermic needle-free vaccination may result in less aversive experience in piglets than did intramuscular vaccination.